The Extent to Which Special Education Students Have the Skills of Scientific Research - Bint Saleh Al-Hmly Saeb Kamel EL Lala, Amal (International Journal of Psychosocial Rehabilitation, 2020)
The present study aimed at revealing the range of knowledge female students of the special education department, faculty of education of Princess Nourah University, have on the skills of scientific research. The study adopted the quantitative approach in collecting and analyzing data. Two measures were developed by the researchers (a questionnaire and an achievement test). The tools of the study were applied to a sample of 344 students of the special education department at different levels and specializations (learning disabilities and autism). The data were analyzed using the statistical package (SPSS). The results showed that the knowledge of scientific research skills female students have was good. The results also indicated that the level of students’ achievement in the achievement test of scientific research skills was weak. The results showed that the perceptions of female students about their knowledge of scientific research skills do not comply with the actual achievement on the achievement test. Several recommendations were presented by the study, including increasing the interest in teaching scientific research courses with non-traditional strategies and increasing scientific research courses in undergraduate study plans.